Characterization of the pathway for transport of the cytoadherence-mediating protein, PfEMP1, to the host cell surface in malaria parasite-infected erythrocytes. - Kriek, N; Tilley, L; Horrocks, P; Pinches, R; Elford, B; Ferguson, D; Lingelbach, K; Newbold, C (2003)
The Plasmodium falciparum erythrocyte membrane protein 1 (PfEMP1) family of antigenically diverse proteins is expressed on the surface of human erythrocytes infected with the malaria parasite P. falciparum, and mediates cytoadherence to the host vascular endothelium. In this report, we show that export of PfEMP1 is slow and inefficient as it takes several hours to traffic newly synthesized proteins to the erythrocyte membrane. Upon removal by trypsin treatment, the surface-exposed population of PfEMP1 is not replenished during subsequent culture indicating that there is no cycling of PfEMP1 between the erythrocyte surface and an intracellular compartment. The role of Maurer's clefts as an intermediate sorting compartment in trafficking of PfEMP1 was investigated using immunoelectron microscopy and proteolytic digestion of streptolysin O-permeabilized parasitized erythrocytes. We show that PfEMP1 is inserted into the Maurer's cleft membrane with the C-terminal domain exposed to the erythrocyte cytoplasm, whereas the N-terminal domain is buried inside the cleft. Transfer of PfEMP1 to the erythrocyte surface appears to involve electron-lucent extensions of the Maurer's clefts. Thus, we have delineated some important aspects of the unusual trafficking mechanism for delivery of this critical parasite virulence factor to the erythrocyte surface.